Does player time-in-game affect tackle technique in elite level rugby union? - Tierney, G. J.; Denvir, K.; Farrell, G.; Simms, C. K. (Journal of Science and Medicine in Sport, 2018)
Objectives: It has been hypothesised that fatigue may be a major factor in tackle-related injury risk in rugby union and hence more injuries occur in the later stages of a game. The aim of this study is to identify changes in ball carrier or tackler proficiency characteristics, using elite level match video data, as player time-in-game increases. Design: Qualitative observational cohort study. Methods: Three 2014/15 European Rugby Champions Cup games were selected for ball carrier and tackler proficiency analysis. Analysis was only conducted on players who started and remained on the field for the entire game. A separate analysis was conducted on 10 randomly selected 2014/15 European Rugby Champions Cup/Pro 12 games to assess the time distribution of tackles throughout a game. A Chi-square test and one-way way ANOVA with post-hoc testing was conducted to identify significant differences (p<0.05) for proficiency characteristics and tackle counts between quarters in the game, respectively. Results: Player time-in-game did not affect tackle proficiency for both the ball carrier and tackler. Any results that showed statistical significance did not indicate a trend of deterioration in proficiency with increased player time-in-game. The time distribution of tackles analysis indicated that more tackles occurring in the final quarter of the game than the first (p = 0.04) and second (p = <0.01). Conclusions: It appears that player time-in-game does not affect tackler or ball carrier tackle technique proficiency at the elite level. More tackles occurring in the final quarter of a game provides an alternative explanation to more tackle-related injuries occurring at this stage.